RUMAH AMAN BAGI KORBAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN DI ACEH (Studi Kasus P2TP2A Provinsi Aceh) - Muslem Abdullah (Universitas Islam Negeri Ar-Raniry, 2019)
Home Safe is a temporary residence that is used to provide protection against victims in accordance with the prescribed standards. Safe house strongly is needed immediately to be built in accordance with the provisions of the law because the victim can tell and feel safe in the safe house. Integrated service center women and Children Empowerment have the task and function to prevent and handle domestic violence that the victims suffer. The problem formulation in this research is that it has not fulfilled the protection of domestic Violence as it has not been formed a safe house in Aceh province. In the discussion of researchers use the type of normative administrative research that is library Research (library) and field research (field) and use qualitative method of data derived from interviews, report notes, documents and others. Based on the research can be obtained the following results: the form of domestic violence that is the cause is economic factors in the family, factors of infidelity, drug factors, the innate factors of the perpetration itself, and Relationship between a married couple who is not balanced. While the P2TP2A effort in reducing domestic violence is to do socialization to Gampong-Gampong to the public about the laws of PKDRT law so that people know about the realm of law that occurs over violence Women. It can be concluded that domestic violence has decreased with the socialization and other performance of the P2TP2A institutions and is advised to immediately build safe houses for victims of domestic violence.